Kindesschutz bei Kindeswohlgefährdung neue Mittel und Wege? - 6. Göttinger Workshop zum Familienrecht - Lipp, Volker; Schumann, Eva; Veit, Barbara (Universitätsverlag Göttingen, 2008)
This volume contains a collection of papers of a October 2007 Göttingen workshop on family law, the upcoming changes of child's welfare by the state in the context of the draft law of the Federal Government to "Facilitate Family Court measures in case of endangered child's welfare.